Predicting and measuring alliance performance: a multidimensional analysis - Lunnan, Randi; Haugland, Sven A. (Strategic Management Journal, 2008)
Abstract The strategic alliance literature demonstrates that alliances create value for the partners, but also that many alliances fall short of expectations. This study addresses the complex issue of alliance performance. We follow 100 contractual alliances over a 5‐year period, and study their performance in terms of abrupt termination, short‐term performance, and long‐term performance. The results indicate that alliances that are considered strategically important are less likely to be abruptly terminated. We also find that newly established alliances have a higher termination rate than older alliances. Short‐term performance is primarily affected by access to complementary and strategically important resources, whereas long‐term performance is related to specific investments in human capital combined with the partners' ability to develop and expand alliance activities over time. Copyright © 2007 John Wiley & Sons, Ltd.